Naticid boreholes on a tertiary cylichnid gastropod from southern Patagonia - Signorelli, Javier Hernan (2006)
The fossil communities are in clear disadvantage when it comes to study the interactions among the species included in them. However, predation on shells gives us the possibility to examine at least some of these interactions. The diameter of the borehole, its placement, and the volume of the prey are parameters that can be easily recorded. Diverse combinations of these may allow inference about the size of the predator and the time spent on the perforation (Kitchell et al., 1981).